2011
DOI: 10.1085/jgp.201110647
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent block of P2X7 receptor channel function is allosteric

Abstract: Among purinergic P2X receptor (P2XR) channels, the P2X7R exhibits the most complex gating kinetics; the binding of orthosteric agonists at the ectodomain induces a conformational change in the receptor complex that favors a gating transition from closed to open and dilated states. Bath Ca2+ affects P2X7R gating through a still uncharacterized mechanism: it could act by reducing the adenosine triphosphate4− (ATP4−) concentration (a form proposed to be the P2X7R orthosteric agonist), as an allosteric modulator, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 38 publications
8
63
0
1
Order By: Relevance
“…This suggests that millimolar (or perhaps micromolar) concentrations of extracellular Ca 2+ and Mg 2+ may act as allosteric inhibitors of murine P2X7 as originally observed for rat P2X7 [46] and established by more recent studies of rat P2X7 [28,29]. The current study also demonstrates that an increase in intracellular Ca 2+ is not essential for P2X7-induced ROS formation (and pore formation) in MEL cells.…”
Section: +supporting
confidence: 77%
“…This suggests that millimolar (or perhaps micromolar) concentrations of extracellular Ca 2+ and Mg 2+ may act as allosteric inhibitors of murine P2X7 as originally observed for rat P2X7 [46] and established by more recent studies of rat P2X7 [28,29]. The current study also demonstrates that an increase in intracellular Ca 2+ is not essential for P2X7-induced ROS formation (and pore formation) in MEL cells.…”
Section: +supporting
confidence: 77%
“…3, A and B). We used ATP because the cost of using millimolar concentrations of BzATP was prohibitive, and because others have shown that ATP and BzATP bind Ca 2ϩ equally well (8 . We calculated the extracellular concentration of free Ca 2ϩ in a given concentration of BzATP or ATP using MaxChelator (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular physiology of the Ca 2ϩ flux is poorly understood despite outstanding recent advances in functional and structural studies (7). This is particularly true for the P2X7 receptor (P2X7R) that is unusually sensitive to allosteric block by extracellular Ca 2ϩ (8), a fact that makes characterization of the Ca 2ϩ component of the ATP-gated current particularly problematic (9,10).…”
Section: Atp-gated P2x7 Receptors Are Prominently Expressed In Inflammentioning
confidence: 99%
“…Two hypothetical mechanisms, namely the gating model and the Pannexin-1 model, have been proposed [3] . In the gating model, pore dilation resulted from longterm ATP action, which leads to additional conformational change [118][119][120][121][122][123][124] . While in the Pannexin-1 model, the conformational changes of the P2X receptor resulted in allosterism of an auxiliary protein coupled with the P2X receptor, such as Pannexin-1, permitting molecules to enter cells through those proteins [125,126] .…”
Section: Questions To Be Answeredmentioning
confidence: 99%